High Mountain Asia hydropower systems threatened by climate-driven landscape instability - Li, Dongfeng; Lu, Xixi; Walling, Desmond E.; Ting Zhang; Steiner, Jakob F.; Wasson, Robert J.; Harrison, Stephan; Nepal, Santosh; Nie, Yong; Immerzeel, Walter W.; Shugar, Dan H.; Koppes, Michèle; et al. (Nature GeoscienceNature Geoscience, 2022)
Global warming-induced melting and thawing of the cryosphere are severely altering the volume and timing of water supplied from High Mountain Asia, adversely affecting downstream food and energy systems that are relied on by billions of people. The construction of more reservoirs designed to regulate streamflow and produce hydropower is a critical part of strategies for adapting to these changes. However, these projects are vulnerable to a complex set of interacting processes that are destabilizing landscapes throughout the region. Ranging in severity and the pace of change, these processes include glacial retreat and detachments, permafrost thaw and associated landslides, rock–ice avalanches, debris flows and outburst floods from glacial lakes and landslide-dammed lakes. The result is large amounts of sediment being mobilized that can fill up reservoirs, cause dam failure and degrade power turbines. Here we recommend forward-looking design and maintenance measures and sustainable sediment management solutions that can help transition towards climate change-resilient dams and reservoirs in High Mountain Asia, in large part based on improved monitoring and prediction of compound and cascading hazards.
Keywords: Climate-change impacts; Hydrology; Natural hazards